Creating feminised critical spaces and co-caring communities of practice outside patriarchal managerial landscapes - Duckworth, Vicky; Lord, Janet; Dunne, Linda; Atkins, Liz; Watmore, Sue (Gender and education, 2016)
The experiences of five female lecturers working in higher education in the UK are explored as they engage in the search for a feminised critical space as a refuge from the masculinised culture of performativity in which they feel constrained and devalued. Email exchanges were used as a form of narrative enquiry that provided opportunity and space to negotiate identities and make meaning from experiences. The exchanges provided a critical space, characterised by trust, honesty and care for the self and for each other, that enabled a sharing of authentic voices and a reaffirming of identities that were made vulnerable through the exposing of the self as an emotional, politicised subject. Drawing on existing theoretical understandings of critical feminised spaces enabled us to create a pedagogical framework for work with students in further developing caring and co-caring communities of practice that are not alternative to, but are outside the performativity landscape of education.